The MURAVES muon telescope: a low power consumption muon tracker for muon radiography applications. Issue 1 (1st November 2022) - D'Errico, M.; Ambrosino, F.; Baccani, G.; Bonechi, L.; Bongi, M.; Bross, A.; Ciaranfi, R.; Cimmino, L.; Ciulli, V.; D'Alessandro, R.; Giudicepietro, F.; Gonzi, S.; et al.
Abstract : Muon Radiography or muography is based on the measurement of the absorption or scattering of cosmic muons, as they pass through the interior of large scale bodies, In particular, absorption muography has been applied to investigate the presence of hidden cavities inside the pyramids or underground, as well as the interior of volcanoes' edifices. The MURAVES project has the challenging aim of investigating the density distribution inside the summit of Mt. Vesuvius. The information, together with that coming from gravimetric measurements, is useful as input to models, to predict how an eruption may develop. The MURAVES apparatus is a robust and low power consumption muon telescope consisting of an array of three identical and independent muon trackers, which provide in a modular way a total sensitive area of three square meters. Each tracker consists of four doublets of planes of plastic scintillator bars with orthogonal orientation, optically coupled to Silicon photomultipliers for the readout of the signal. The muon telescope has been installed on the slope of the volcano and has collected a first set of data, which are being analyzed.